Application of Listening Reading Technique in Improving the Ability to Read the “Kitab Kuning” of Santri - Bambang Irawan (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2020)
This article is the result of a research study that discusses the Application of Reading Reading Techniques in Improving the Ability to Read the “kitab kuning” of Santri Putri at the Pondok Pesantren Bustanul Ulum Melokorejo, Jember Regency. Based on data analysis, it can be concluded that the application of reading reading techniques in improving the reading ability of the santri book is a teaching method that presents subject matter that begins with prioritizing aspects of reading, i.e. the teacher first reads the reading topics, then is followed by the santri. However, sometimes the teacher directly appoints one of the students to read an individual lesson first, and of course, the other students pay attention and follow it. The method of reading besides emphasizing reading ability also considers the importance of correct pronunciation. So this ability is seen to help the students to improve their ability to read the book.